2015
DOI: 10.1590/2177-6709.20.6.037-042.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fluoride sealant in the prevention of carious lesions around orthodontic brackets: an OCT evaluation

Abstract: Objective: This article aimed to evaluate in vitro the efficiency of Pro Seal fluoride sealant application in the prevention of white spot lesions around orthodontic brackets. Material and Methods: Brackets were bonded to the buccal surface of bovine incisors, and five groups were formed (n = 15) according to the exposure of teeth to oral hygiene substances and the application of enamel sealant: G1 (control), only brushing was performed with 1.450 ppm fluoride; G2 (control) brushing associated with the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Enamel demineralization around orthodontic appliances continues to be a common clinical problem, even in face of the application of fluoridated materials, which minimize but do not solve the problem completely. [1][2][3]7,8 The present study tested in situ a product containing fluoride and nano-hydroxyapatite that reduced demineralization around brackets (Tables 1, 3, 5 and 7), confirming fluoride role on such protection. The in situ model with intraoral devices has been frequently used, as it simulates the caries process that occurs within the oral cavity.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Enamel demineralization around orthodontic appliances continues to be a common clinical problem, even in face of the application of fluoridated materials, which minimize but do not solve the problem completely. [1][2][3]7,8 The present study tested in situ a product containing fluoride and nano-hydroxyapatite that reduced demineralization around brackets (Tables 1, 3, 5 and 7), confirming fluoride role on such protection. The in situ model with intraoral devices has been frequently used, as it simulates the caries process that occurs within the oral cavity.…”
Section: Discussionsupporting
confidence: 54%
“…Previous in vitro and in vivo studies have already demonstrated a demineralization preventive or reducing potential of fluoride-containing products. 3,7,8,21,22 Other studies indicated that preventive programs that use daily fluoride mouthrinses 1,2 may protect the orthodontic patient from white spots, but they are dependent on the cooperation of the patients to achieve such an objective. The topical application of varnishes containing 5000 ppm of fluoride is advantageous in this respect, as it only depends on the professional application, reducing the influence of patient cooperation on the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors are already interested in the topic of OCT imaging in the field of orthodontics, proving our hypothesis that OCT should be incorporated into clinical diagnostics. 19,[36][37][38][39][40]…”
Section: Discussionmentioning
confidence: 99%
“…Application of OCT as a non-invasive imaging tool has been used in ophthalmology (Carrasco-Zevallos et al, 2016;Zhang et al, 2016;Shirazi et al, 2017), agronomy (Ravichandran et al, 2016a(Ravichandran et al, , 2016bWijesinghe et al, 2017), entomology (Choi et al, 2017;Ravichandran et al, 2017), and industrial inspection (Shirazi et al, 2016) and has been studied for more than two decades. In the field of orthodontics, it has proven to be of value for visualization of changes in the enamel surface after routine orthodontic de-bonding and various demineralization procedures (Koprowski et al, 2014;Pithon et al, 2015;Wijesinghe et al, 2016;Seeliger et al, 2017). The ability of the system to provide a 3-dimensional (3D) image and also 2-dimensional (2D) images with high sub-micron resolution is of note.…”
Section: Introductionmentioning
confidence: 99%